Working Class Credit and Community since 1918 - Taylor, A. author. aut Link
X, 218 p.
Keywords: This book explores the forms of credit which have historically been associated with the British working class. Taylor seeks to assess the effect of credit on working class communities, and relates this to the debate about community. This work is the first comprehensive examination of the history of these forms of credit to make comparisons between the periods before and after 1945. Based on extensive archival research and oral history interviews, this book combines lively individual accounts with theoretical arguments.